PENGARUH SWEDISH BACK MASSAGE TERHADAP PENGELUARAN AIR SUSU IBU - Inggrid Dwi Wahyuni; Oswati Hasanah; Wan Nishfa Dewi (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Keperawatan, 2018)
Breast milk ejection is a very complex interaction between stimulation and hormonal regulation. Swedish back massage has become an alternative therapy to increase breast milk production and breast milk ejection. Touching in massage is very important in the stimulation of oxytocin hormone stimulation process. The aim of this study was to determine the effect of Swedish back massage on breast milk ejection. This study was conducted in the Community Health Center in Harapan Raya Pekanbaru by using quasy experiment and non-randomized control group pre-test-post-test. Was taken with purposive sampling for 34 respondents devided into 17 respondents for the experimental group and 17 respondents for the control group. The experiment group intervention gave along 3 days attending to 15 minutes Swedish back massage. Measuring equipment in this study used the indicator sheet that assesses breast milk ejection.Bivariate analyzed by using Wilcoxon and Mann-Whitney test. The result showed that (p value = 0,021) for experimental group and (p value = 1,000) for controlling group. This result showed us that the Swedish back massage gives a positive effect on breast milk ejection. The swedish back massage of this study is expected to be one of the nursing interventions to increase the breast milk ejection.Key word : Breast milk ejection, massage, oxytocin hormone, swedish back massage